Turbulent Flow and Heat Transfer Problem in the Electromagnetic Continuous Casting Process - Mookum, T.; Wiwatanapataphee, B.; Wu, Yong Hong (World Scientific and Engineering Academy and Society (WSEAS), 2011)
This paper aims to study the effect of turbulence on the flow of two fluids and the heat transfer-solidification process in electromagnetic continuous steel casting. The complete set of field equations is established. The flow pattern of the fluids, the meniscus shape and temperature field as well as solidification profiles obtained from the model with and with no turbulence effect are presented. The results show that the model with turbulence gives a large circulation zone above the jet, much larger variation of the meniscus geometry, a slow solidification rate and higher temperature in the top part of the strand region.